Soundscape and the Adaptation of Soundscape to Covered Spaces - Ozcevik, Asli; Can, Zerhan Yuksel (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2011)
Soundscape, as urban noise is termed, is essentially a qualitative approach which aims to discover ways to improve the sonic environment. A possible analogy can be assumed for the acoustic quality of some types of covered spaces which have a function similar to urban spaces. Furthermore, it can be proposed that such covered spaces may have a specific, distinct and recognizable sound environment - hence, a soundscape occurs which is created both by the architecture and the sound sources. This study takes a further step in suggesting that the acoustic comfort or sound quality of these spaces cannot be sufficiently dealt with via noise parameters. This paper aims to show the possibility of evaluating the acoustical quality of covered spaces, such as shopping centers, through soundscape studies. The formation of streets is the basic spatial design concept that connects open and closed shopping areas. For this reason the researchers chose to study a modern and an historical shopping center and a modern and a traditional street, both of which have shopping as a basic function, The soundscapes of these open and closed shopping areas were determined by soundwalks and listening tests. The objective and subjective findings of this study showed that covered shopping areas have a specific soundscape that can be evaluated by the soundwalk method regardless of whether the environment is open or covered.
Keywords: Soundscape; urban acoustic comfort; acoustic comfort in covered spaces; Architecture